Writing and Implementing an Open Textbook in World Regional Geography: A Case Study - Caitlin Finlayson (Athabasca University Press, 2020)
As the rising cost of college textbooks has outpaced both inflation and increases in tuition fees, this expense has created a significant barrier to student learning. Some instructors have adopted or created open educational resources, meaning materials which are freely and openly available. While the most obvious benefit of open course content might be cost savings, the fact that these materials can be freely adapted and changed can have substantial impact on the learning experience itself and enable an instructor to completely change the structure and outcomes of a course. This paper provides a case study on writing an open textbook for a course called World Regional Geography and details the writing process and platform options. I also offer practical guidance for faculty interested in authoring open materials and insight into how writing open materials might be framed in terms of a faculty member’s larger portfolio of professional activity.